Cover Image, Volume 528, Issue 4. Issue 4 (6th January 2020) - Kalambogias, John; Chen, Chia‐Chien; Khan, Safraz; Son, Titus; Wercberger, Racheli; Headlam, Carolyn; Lin, Cindy; Brumberg, Joshua C.
Abstract : The cover image is based on the Original Article Development and Sensory Experience Dependent Regulation of Microglia in Barrel Cortex by Joshua C. Brumberg et al., https://doi.org/10.1002/cne.24771 .